Risk Management in Future Romanian E-government 2.0 Projects - Didraga, Otniel (Studia Universitatis Vasile Goldiș Arad, Seria Științe Economice, 2015)
E-government public services in Romania must follow unitary procedures considering the new requirements of the European Union from the Digital Agenda for Europe Strategy 2020. E-government 2.0 has to be implemented because of the cultural and behavioral transformations in the interaction between governments and users of e-services. E-government 2.0 projects use tools and techniques of social media to accomplish their goals. This article examines the possible risk categories and the risk management procedures needed to mitigate risks in future Romanian e-government projects, according to the strategic lines of development for the Digital Agenda. We propose a risk management plan for the e-government lines of action within the strategic lines of development that includes identifying, assessing, and mitigating the risks. New and modernized government services through e-government 2.0 projects that apply risk management will bring a significant improvement in how citizens and businesses relate to government and will increase the use of e-government services.